PENGARUH FAKTOR KEPRIBADIAN PEGAWAI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR REGIONAL XII BKN PEKANBARU - Indarti, Sri; Hendriani, Susi; Mahda, Mutia (Jurnal Ekonomi, 2014)
This study aims to investigate the influence of personality and environmentalfactors on the performance of employees working at the Regional Office XII BKNPekanbaru. The analytical method used in this research is descriptive statisticalanalysis method and multiple linear regression analysis.This research uses a survey method, where as many as 48 employees weresampled prior to hypothesis testing, the primary data questionnaire validity andtested first realibitasnya using SPSS version 17. The regression equation was thentested with analysis of classical assumption of normality test, multicollinearity,heteroscedasticity test, autocorrelation test and linearity test analysis of therelationship of independent variables with the dependent variable is done byanalysis of t test, F test, determinant coefficient ( adjusted R 2 ) and correlationcoefficient ( R ).The results showed an employee’s personality and work environmentsimultaneously (together) have a significant effect on the performance ofemployees in an employee’s personality persial significant effect on theperformance of employees, where the indicator accuracy (conscientiousness) andbreadth indicators (extraversion). For the working environment persialsignificant effect on the performance of employees, where the physical workenvironment indicator gets low value that needs to be done to repair the physicalworking conditions.Kata Kunci : Employee Personality,Work Environment,Employee Performance